SELECTION OF SCIENCE OLYMPIAN USING ANALYTICAL HIERARCHICAL PROCESS METHODS - Dicky Apdilah (INFOKUM, 2021)
Decision Support System is an interactive system, which helps decision makers through the use of data and decision models to solve semi-structured and unstructured problems. Analytical Hierarchy Process (AHP) is a decision support model developed by Thomas L. Saaty, a mathematician. This decision support model will solve complex problems by structuring a hierarchy of criteria, stakeholders, results and by drawing various considerations to develop weights or priorities.